2014
DOI: 10.1007/s00248-014-0431-4
|View full text |Cite
|
Sign up to set email alerts
|

Microbial Characterization of Microbial Ecosystems Associated to Evaporites Domes of Gypsum in Salar de Llamara in Atacama Desert

Abstract: The Central Andes in northern Chile contains a large number of closed basins whose central depression is occupied by saline lakes and salt crusts (salars). One of these basins is Salar de Llamara (850 m a.s.l.), where large domed structures of seemingly evaporitic origin forming domes can be found. In this work, we performed a detailed microbial characterization of these domes. Mineralogical studies revealed gypsum (CaSO(4)) as a major component. Microbial communities associated to these structures were analys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
61
1
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 66 publications
(76 citation statements)
references
References 38 publications
13
61
1
1
Order By: Relevance
“…It is known that hypersaline environments have a low diversity, where halophilic microorganisms are able to survive to these extreme conditions because they have specific strategies to balance the osmotic pressure [32,33]. Moreover, it has been seen that these systems usually have very low organic carbon and nitrogen content [8,25,30,34]. The combination of these factors makes soils from these environments inhabitable only by a very low diversity of organisms, mostly bacteria and archaea, but also some fungi and protists [25,34,35].…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…It is known that hypersaline environments have a low diversity, where halophilic microorganisms are able to survive to these extreme conditions because they have specific strategies to balance the osmotic pressure [32,33]. Moreover, it has been seen that these systems usually have very low organic carbon and nitrogen content [8,25,30,34]. The combination of these factors makes soils from these environments inhabitable only by a very low diversity of organisms, mostly bacteria and archaea, but also some fungi and protists [25,34,35].…”
Section: Discussionmentioning
confidence: 98%
“…The CCA triplot revealed significant correlations to the ten most abundant phyla detected in each sample studied. Besides, the analysis of three evaporite samples was included, two from Laguna LLamara [8] and one from Laguna Tebenquiche [9], in order to observe differences among areas. CCA axes 1 and 2 explain 77 % of total variance of the data.…”
Section: Multivariate Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Oscillatoriales, Synechococcus, Cyanothece and Gloeocapsa groups and genus Gloeobacter) in the salar de Llamara, a salt flat basin (Salar de Llamara) located in the Atacama desert (Demergasso et al 2003). Additionally, photosynthetic pigments were detected being more diverse on the upper photosynthetic layer associated to evaporites domes of gypsum in the Salar de Llamara, where cyanobacteria and diatoms species were also detected (Rasuk et al 2014). However, there is little information about cyanobacterial communities under hypersaline condition (Dorador et al 2008).…”
Section: Extreme Photosynthetic Communitiesmentioning
confidence: 99%
“…Similarly, many studies have investigated the Atacama Desert (Desierto de Atacama) located as a plateau in South America along the Pacific coast to the west of the Andes mountains. It is the driest, non-polar and oldest desert on Earth (Farías et al 2014;Rasuk et al 2014Rasuk et al , 2016. Recent findings (Rasuk et al 2016) have indicated that a large proportion of 16S sequences could not be classified at the phylum level, which may indicate a new phylum is present in this Desert.…”
Section: Introductionmentioning
confidence: 99%